Penerapan Alat Peraga Kartu Berpasangan Untuk Meningkatkan Hasil Belajar Kimia Materi Pokok Ikatan Ion Kelas X MIPA 3 MAN 1 Grobogan - Mukhoyyarotul Jannah (Lembaga Pengembangan Kinerja Dosen, 2024)
This researchx generally iaims to improvex the learning joutcomes of class And xspecifically, it aims to censure that students are able to dachieve learning goals by xproducing a minimumx KKM score of 70 and a minimumx of 80% of the totalx numberd of students are cable to achieveq this minimum limit. The research imethod used in this researchi is the Classroomf Action xResearch Method or better vknown as the Classroomx Action Researchi (PTK) method. The PTK methodf is a processg of assessingy learning problemsx in the classroomo throughi self-reflectionf in an effortg to resolveu these problems by xcarrying out plannedg actions in real situations and janalyzing any uimpacts of the dtreatment. The results of researchd conductedf in class That the applicationt of pairedw card teachingf aids can ximprove students' chemistry dlearning goutcomes, especially in ionic bonding material.